Integration of smart watch and Geographic Information System (GIS) to identify post-earthquake critical rescue area part. I. Development of the system. (October 2020) - Hossain, M.S.; Gadagamma, C.K.; Bhattacharya, Y.; Numada, M.; Morimura, N.; Meguro, K.
Abstract: In this research, a new system is developed to aid the existing emergency response practices after a massive earthquake, hereafter called the Earthquake Emergency Micro Response System (EEMRS). This system can observe the post-earthquake situations by integrating smart watch data using exposed population with Geographic Information System (GIS). A smart watch is a potential tool to dissipate the information of the location and health condition of a potential victim. A methodology is developed to identify trapped victims and critical rescue area using the data dissipated by smart watches of potential victims and exposed elements. The developed method is capable to capture the victims and rescue the operations by identifying the critical rescue area in the shortest possible time by tracking victims' heart rate and movement. Medical team expert's opinions were used to evaluate the method and increase the effeciency of system, and to validate the model a hypothetical earthquake scenario is developed to emphasize and analyze the immediate situation. The aim of the developed system is to enhance efficiency, speed and proper location tracking to enable more victims to be rescued in an earthquake situation.